STRATEGIC ADJUSTMENT OF RUSSIA, THE UNITED STATES, CHINA AND VIETNAM’S RESPONSE - Yen, Pham Thi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This article aims to assess the strategic shifts of Russia, the US, and China since the early 21st century and analyze Vietnam's corresponding responses. Utilizing two established methodologies in international relations research—policy analysis and historical research—the author seeks to provide clarity on the subject. The policy analysis method aids in understanding a nation's motives, interests, and actions by examining its implemented policies, while the historical research method offers a comprehensive view by organizing events and data chronologically and spatially. Findings suggest that Russia, influenced by events like the Ukraine conflict, has strengthened ties with China, while China and the US have adopted more adaptable strategies to extend their global influence. These adjustments, with a shared focus on the Asia-Pacific region, hold implications for Southeast Asian countries, particularly Vietnam. Amidst global complexities, Vietnam maintains its commitment to independent foreign policy, pursuing a "dynamic balance" with major powers. The article concludes that due to strategic interest conflicts, competition among these nations will persist, prompting Vietnam to maintain a balanced diplomatic approach, even if it involves navigating delicate relationships—a metaphorical "tightrope" of equilibrium amidst uncertainty